2021
DOI: 10.1136/bmjopen-2020-043358
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cost evaluation of intensive support team (IST) models for adults with intellectual disabilities who display challenging behaviour: a comparative cohort study protocol

Abstract: IntroductionApproximately 17% of adults with intellectual disabilities (ID) living in the community display behaviours that challenge. Intensive support teams (ISTs) have been recommended to provide high-quality responsive care aimed at avoiding unnecessary admissions and reducing lengthy inpatient stays in England. We have identified two models of ISTs (model 1: enhanced provision and model 2: independent provision). This study aims to investigate the clinical and cost-effectiveness of the two models of ISTs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This is the first study in our knowledge to explore the views and experiences of multiple stakeholders of IST care in England. This qualitative study is part of a wider research programme that provided an overview of the current operation of ISTs and evaluated the clinical and cost effectiveness of two IST models in England (Hassiotis et al, 2021, 2022). Findings suggest that ISTs are often well received by family and paid carers and adults with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first study in our knowledge to explore the views and experiences of multiple stakeholders of IST care in England. This qualitative study is part of a wider research programme that provided an overview of the current operation of ISTs and evaluated the clinical and cost effectiveness of two IST models in England (Hassiotis et al, 2021, 2022). Findings suggest that ISTs are often well received by family and paid carers and adults with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In phase two of the larger study (Hassiotis et al, 2021), 21 ISTs were enrolled, of which seven case study sites were selected for the current qualitative study. These were selected to include both IST service models (enhanced and independent), and to capture other forms of service variability within each model, including location in rural or urban areas, caseload size, funding arrangements, and length of service existence (see Supplementary Material S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that there are 1.5 million people in the UK with an intellectual disability (Hassiotis et al , 2021), of whom approximately 1.1 million are adults (Mencap, 2021). As few as 1 in 4 people with intellectual disabilities (ID) may be formally registered with health services (Hatton et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…What is the efficacy of PBS in supporting people with CB that is of high frequency and/or severity (LaVigna and Willis, 2012)? Studies have demonstrated the effectiveness of PBS in reducing behaviours that are both high in frequency and intensity (Hassiotis et al , 2021) and low in frequency in both community and inpatient settings (Hastings et al , 2013). The framework is cost-effective and easily accessible when supporting carers to apply the taught skills to help service-users to enhance their QoL (Grey et al , 2016).…”
Section: Introductionmentioning
confidence: 99%